Allium urusakiorum (Amaryllidaceae), a new member of the Balkan clade of the section Oreiprason from European Turkey - Koçyiğit, Mine; Seregin, Alexey P.; Özhatay, Neriman; Friesen, Nikolai (Phytotaxa, 2016)
The taxonomy of the Allium saxatile group (sect. Oreiprason) has been studied recently upon morphological and molecular data. New specimens collected from the European part of Turkey near the Istranca Mountains and identified as ‘A. saxatile’ proved to be a new species confirmed by sequences of internal transcribed spacer (ITS) and two plastid DNA regions (rpl32–trnL and trnL–trnF) and supported by morphological characters. Allium urusakiorum, a new species from the A. saxatile group, is described here through living and herbarium specimens. It is the only species of the sect. Oreiprason in the country and seems to be an endemic species of the Turkish flora. Characteristics of the species include morphological description, identification key, molecular dataset, and karyotype (2n = 16).